Eysenck's temperament typology and evoked potentials - Tatalović Vorkapić, Sanja (Array, 2009)
The aim of this research was to analyze the relationship between parameters of evoked potentials (N1, P2, N2, P3 and Sw) elicited by visual oddball paradigm and levels of neuroticism and psychoticism measured by EPQ-R, and level of depression measured by D-92. One of the reasons for conducting this kind of study is a very small number of studies showing inconsistent results. Nevertheless, on the basis of earlier findings, it was assumed that more depressed students would show longer EP-latencies, and that higher neuroticism and psychoticism would be associated with smaller EP-amplitudes. The participants were psychology students (N=54), all female, age 19-23, right-handed, without any known psychiatric/neurological disorders. In the first trial, significant negative correlations between neuroticism and P2 amplitude measured on P3 (r=-.28, p=.04) and P4 (r=-.31, p=.02), as well as a significant positive correlation between neuroticism and P3 amplitude measured on P3 (r=.28, p=.04) have been found. In the second trial, significant negative correlation between neuroticism and N2 amplitude (r=-.31, p=.02) and neuroticism and P2 amplitude (r=-.33, p=.02) measured on P4 have been determined, as well as significant positive correlation between psychoticism and N2 amplitude measured on P4 (r=.37, p=.01) and P3 amplitude measured on P3 (r=.37, p=.01) and P4 (r=.33, p=.02). Thus, students with higher neuroticism have shown significantly lower amplitudes of the potentials representing early stimuli processing (P2) and stimuli characteristics assignment (N2). The relationship between neuroticism and P2 amplitude proved to be the most stable one as it was determined in both trials. Students with higher psychoticism showed significantly higher amplitudes of N2 and P3, representing attention allocation and memory updating. The level of depression correlated only with a slow wave latency measured on P3 (r=.33, p=.01) and on P4 (r=.34, p=.01), confirming the hypothesis that more depressed students would show significantly longer EP-latencies. The findings are discussed in the frame of Eysenck’s personality theory and the overarousal hypothesis.